Monochromatic HDR photography : shooting and processing black & w hite high dynamic range photos - Davis, Harold, 1953- (New York : Focal Press, Taylor Francis Group, 2014)
"Monochromatic HDR Photography is the first book intended to show ph otographers how to work at the intersection of two up-and-coming trends that are at the forefront of the digital revolution: Black & White and High Dynamic Range imaging. The book explains techniques for extending dynamic range, monochromatic conversion methods and best practices whe re the two technologies intersect. Since successful digital monochromat ic image creation generally requires using the color information inhere nt in RAW exposures, most case studies will be presented in full color. In addition, Monochromatic HDR Photography provides extensive coverage of the creative vision required to successfully create monochromatic HD R images and the workflow necessary to make art prints from this specia lized image making technique"--
Includes bibliographical references (p.204-205) and index.
Keywords: High dynamic range imaging; Black-and-white photography; PHOTOGRAPHY / Techniques / Digital (see also COMPUTERS / Digital Med ia / Photography).; PHOTOGRAPHY / Techniques / General